Natural P-gp inhibitor EGCG improves the acteoside absorption in Caco-2 cell monolayers and increases the oral bioavailability of acteoside in rats. (December 2020) - Zhou, Fei; Huang, Weisu; Xu, Tao; Wu, Lipeng; Chen, Qi; Peng, Jiyu; Liu, Xin; Lu, Baiyi
Abstract: Acteoside is one of the most widespread phenylethanoid glycosides with pharmacological activities, including antioxidant, neuroprotective property, etc. However, its bioavailability is poor due to the low absorption and P-gp efflux. This study aimed to select food derived P-gp inhibitors for promoting the acteoside absorption and investigate whether the inhibitors could increase the bioavailability and stability of acteoside. Results showed that EGCG and quercetin significantly decreased the BL-to-AP efflux and promoted the AP-to-BL influx of acteoside across Caco-2 monolayers with optimum concentrations of 320 μM EGCG or 240 μM quercetin adding to 320 μM acteoside. EGCG increased the bioavailability of acteoside to 1.43-fold, but quercetin had no such effect. Further study showed that EGCG and quercetin had no effects on the storage and digestion stability of acteoside. This work revealed that EGCG could improve the acteoside absorption across the Caco-2 monolayers and enhance the bioavailability of acteoside in rats. Highlights: EGCG and quercetin decreased the efflux and promoted the influx of acteoside. Adding 320 μM EGCG or 240 μM quercetin enhanced acteoside absorption optimally. EGCG increased the bioavailability of acteoside in rats to 1.43-fold.